2016
DOI: 10.1016/j.bjm.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane trash levels in soil affects the fungi but not bacteria in a short-term field experiment

Abstract: The sugarcane in Brazil is passing through a management transition that is leading to the abolition of pre-harvest burning. Without burning, large amounts of sugarcane trash is generated, and there is a discussion regarding the utilization of this biomass in the industry versus keeping it in the field to improve soil quality. To study the effects of the trash removal on soil quality, we established an experimental sugarcane plantation with different levels of trash over the soil (0%, 50% and 100% of the origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…Rachid et al . () observed that straw removal modified the fungal communities present in soil, but did not affect bacterial communities. However, other studies have shown that microbial communities can be shaped by straw management as well as through the addition of organic or mineral fertilizers (Rachid et al ., ; Navarrete et al ., ; Pitombo et al ., ).…”
Section: Impacts Of Straw Removal On Soil Biological Attributesmentioning
confidence: 97%
See 1 more Smart Citation
“…Rachid et al . () observed that straw removal modified the fungal communities present in soil, but did not affect bacterial communities. However, other studies have shown that microbial communities can be shaped by straw management as well as through the addition of organic or mineral fertilizers (Rachid et al ., ; Navarrete et al ., ; Pitombo et al ., ).…”
Section: Impacts Of Straw Removal On Soil Biological Attributesmentioning
confidence: 97%
“…Recently, there have been efforts to characterize the microbial groups responsible for the soil activities under various management practices in sugarcane cropping areas (Navarrete et al ., ; Pitombo et al ., ; Rachid et al ., ). Rachid et al .…”
Section: Impacts Of Straw Removal On Soil Biological Attributesmentioning
confidence: 97%
“…Several studies conducted around the world have shown that the maintenance of sugarcane straw promotes increases in microbial biomass (Graham and Haynes, 2006;Souza et al, 2012;Paredes Jr. et al, 2015) and microbial community diversity (Rachid et al, 2013(Rachid et al, , 2016Liao et al, 2014), especially in surface soil layers. In terms of soil macrofauna, despite the land-use change sequence, native vegetation-pasture-sugarcane induces a significant reduction in the diversity of macroinvertebrates , the remaining straw support the soil biota as a food source, improving microclimate conditions and as a shelter in sugarcane areas (Portilho et al, 2011;Benazzi et al, 2013).…”
Section: Iii) Crop Residues Vs Soil Biological Propertiesmentioning
confidence: 99%
“…Organic material and nitrogen content were moderately high (Table 1). Analyzed soil satisfied the physicochemical conditions required for sugarcane harvest and showed similar parameters to Brazilian soil sown with this crop (Rachid et al, 2012;Rachid et al, 2016). Therefore, these data could be used as reference in sugarcane production in Mexico.…”
Section: Soil Physico-chemical Characteristicsmentioning
confidence: 60%